Study of thyroid dysfunction and dyslipidemia in chronic kidney diseases - Tripathy, S. K.; Dhal, N.; Kanungo, M.; Das, S.; K. Mishra, S.; Swaroop, Sai; R. Behera, M.; Panigrahi, M. (International Journal of Research in Medical Sciences, 2017)
Background: Though there are many studies on thyroid dysfunction and dyslipidemia in Chronic Kidney Disease (CKD), no study is conclusive. Aim of this study was to correlate abnormalities in thyroid function and lipid profile with the severity of renal failure and also to observe the difference of these abnormalities between patients on conservative management verses hemodialysis. Methods: Hundred consecutive CKD cases admitted to Medicine Department were taken up for the study. They were divided into two groups as Group-A [on conservative management] and Group-B [on regular Hemodialysis (HD)]. Hundred healthy persons were taken as control in Group-C. After evaluation of thyroid function and lipid profile statistical analysis was done by students t-test, chi-square and regression analysis. Results: Hundred CKD cases with 74% male (n=74) and 26% female (n=26) in a M: F ratio of 2.9:1 were found to be in different stages CKD (0, 2, 20, 28 and 50 in stage-1 to stage-5 respectively). In 50 cases of stage-5 CKD, 30 were on HD and 20 on conservative management. Diabetes Mellitus (DM) (40%) was the commonest etiology of CKD followed by Hypertension (HTN), obstructive uropathy, chronic glomerulonephritis (CGN) and polycystic kidney disease (PKD). Thyromegaly was not found in a single case. In all CKD cases (Group-A+B) TT3 (TT3) was significantly low (P =0.0011) when compared with control (Group-C) and no difference was found between Group-A and Group-B. Fall in TT3 worsened with increasing severity of CKD. Lipid profile study revealed Decreased High-Density Lipoprotein Cholesterol (HDLc) and increased Triglyceride (TG), Total Cholesterol (TC), Low Density Lipoprotein Cholesterol (LDLc), TC/HDLc and LDLc/HDLc in Group-A than Group-B but only TG and TC increase was statistically significant. The levels of TG and TC and TC/HDLc increased as the stage of CKD progressed and was statistically significant (P= 0.035). Conclusions: There occurs a state of biochemical hypothyroidism without overt clinical hypothyroid state in CKD, the extent of which correlates with the severity of CKD. Increased cardiovascular complications occur due to accelerated atherosclerosis in CKD. This study confirmed that atherogenic lipid profile and thyroid dysfunction worsen with the progression of disease. Difference between patients on conservative management and HD was not found.